Evaluation and Projection of Interdependence Between the Social and Economic Situation in the Region and the Structure and Dynamics of Labor Migration - V. Guskova, I.; E. Serebrovskaya, N.; O. Grudzinskii, A.; V. Petrova, O. (International Journal of Engineering and Technology, 2018)
The article analyzes the existing approaches to assessing the impact of labor migration on the state and functioning of the labor market. The authors developed a methodology for assessing the dependence of the scale of labor migration on the social and economic factors of the region, such as the level of economic development, the level of accessibility of medical and social services, the level of material well-being, and the level of spiritual development. These factors are determined by the statistical indicators for the Volga Federal District (VFD) and ranked by an expert survey. This methodology allows predicting the extent and direction of migration flows based on the data of a specific region.